PENINGKATAN HASIL BELAJAR SISWA KELAS III SDI FATUKOA TENTANG PENJUMLAHAN DAN PENGURANGAN PECAHAN MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN MEDIA BLOK PECAHAN - Adam Bol Nifu Benu; Damianus Dao Samo; Olivia Mariana Cardoso (Universitas Nusa Cendana, 2023)
This study aims to improve the learning outcomes of class III A SD Inpres Fatukoa in the material of adding and subtracting fractions using the STAD-type cooperative learning model with the help of fractional block media. The subjects in this study amounted to 31 students. This study used classroom action research which consisted of four stages, namely planning, implementing, observing, and reflecting. Data collection techniques used are observation, tests, and data analysis techniques used are descriptive and qualitative. The results of the data analysis showed that the results of teacher activities in the first cycle obtained an average value of 78.57% and in the second cycle, it increased to 92.85%. Then the results of observing student activity in the first cycle obtained a class success score of 72.04 and in the second cycle, it increased to 87.81. Meanwhile, student learning outcomes in cycle I obtained an average class score of 74.36 with a completeness percentage of 64.51% and in cycle II it became 85.94 with a completeness percentage of 90.31%. So it can be concluded that the use of the STAD-type cooperative learning model with the help of fractional block media can improve student learning outcomes